Strengths, Weaknesses, Opportunities, and Threats Analysis of Strategies to Improve School Competitiveness in Coastal Areas - Setiawan, Endry; Nurlaili; Handayani, Ninik; Hermansyah; Setiono, Ranto (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2024)
The competitiveness of schools in coastal areas often face significant challenges due to geographical isolation, limited resources and environmental threats. This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) of strategies to improve the competitiveness of schools in coastal areas of Berau Regency. Using a mixed-methods approach, this research combines quantitative SWOT analysis with qualitative data from interviews, observations, and document review to provide a comprehensive understanding of the internal and external factors affecting school performance. The results show that schools have strengths such as strategic geographic accessibility, strong relationships with local communities, and effective use of technology. However, weaknesses such as inadequate facilities and limited professional development for teachers, coupled with threats such as environmental degradation and budget constraints, hinder their growth. Positioned in Quadrant I of the SWOT matrix, schools are in a favorable position to adopt growth-oriented strategies by leveraging their strengths to capitalize on opportunities. The study concludes that targeted interventions, such as expanding digital infrastructure and promoting ecosystem-based learning programs, are critical to enhancing competitiveness. These findings provide actionable insights for policymakers and educators to address challenges and optimize educational outcomes in similar coastal regions.